Sustainability Transition in Bali Tourism: Thematic Trends and Governance Gaps - Made Herry Erika; Jery Christianto; Dinar Sukma Pramesti (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study explores the dynamics of sustainable tourism in Bali from 2022 to 2026, a critical period for post-pandemic recovery and paradigm shifting. Using a qualitative thematic analysis approach, the study reviewed 30 peer-reviewed journal articles published between 2022 and 2026. The articles were identified through a systematic search of the Google Scholar database using keywords related to sustainable tourism in Bali and were selected based on relevance to sustainability practices, governance, environmental management, and cultural preservation. Findings reveal a significant transition toward community-based and spiritual tourism models, driven by local wisdom such as Tri Hita Karana. However, the analysis identifies a persistent 'institutional gap' caused by regulatory fragmentation between governmental authorities and traditional village leadership (Desa Adat). While ecological crises have accelerated the adoption of decarbonization strategies, digital technology integration remains a double-edged sword, risking cultural commodification. This study contributes to the sustainable tourism literature by providing a thematic synthesis of recent research and highlighting the importance of governance coordination, environmental management, and culturally sensitive digital innovation in supporting sustainable tourism development in Bali.